The impact of carbon footprint labels and QR code traceability on consumers’ willingness to pay: Evidence from a discrete choice experiment in urban Vietnam - Yen, Do Hai; Chi, Phan Hoang Quynh (International journal of economic perspectives, 2025)
This study investigates how carbon footprint labels and QR code traceability influence consumers’ willingness to pay (WTP) for food and beverage products in urban Vietnam. Using a discrete choice experiment with 400 respondents from Hanoi and Ho Chi Minh City, the research estimates both conditional logit and mixed logit models to measure the marginal value of labeling attributes. Results reveal that consumers are willing to pay 9.8 percent more for products with carbon labels, 7.2 percent for QR traceability, and 11.6 percent for third-party verification. When both carbon and QR information are presented together, the combined WTP rises to 15.3 percent, confirming a complementary effect between environmental and digital transparency. Heterogeneity analysis shows that consumers with higher income and stronger environmental concern demonstrate significantly greater WTP. These findings suggest that transparency mechanisms not only enhance consumer trust but also provide strategic opportunities for firms and policymakers to promote sustainable consumption in Vietnam.